Tinjauan Hukum Terkait Peraturan Bupati Inhil Tentang Pemberian Izin Angkringan Di Kota Tembilahan Dari Perspektif Filsafat Hukum Islam - Siti Rahmah; Tia Juliana; Besse Dina Maria Oktavia; Nurayiyin; Muanif Ridwan (Universitas Islam Indragiri, 2025)
The food and beverage business is one type of business that is widely considered by the public, especially Gen Z. Because food and beverages are basic daily needs for every individual, it is not surprising that in the city of Tembilahan there are so many restaurants, cafes, angkringan and the like. The culinary business itself is easy to establish because it is simple and the capital required is very varied and does not require high technical skills to run it. The term angkringan comes from the Javanese language, angkring, which means a tool and place for selling food that is carried on the shoulder and has a curved shape. Besides curved, angkringan also has a pushcart shape, as we often see on the outskirts of the city. This angkringan is now widely found in other cities, including the city of Tembilahan. Angkringan stalls were first introduced by someone named Mbah Pairo. This study aims to examine the Indragiri Hilir (Inhil) Regent's Regulation that regulates the granting of operational permits for angkringan, especially in public locations such as Jalan Hang Tuah Tembilahan, on Jalan M. Boya Tembilhan from the perspective of Islamic legal philosophy (FHI). The regulation, which tends to lead to policies on organizing, protecting, and providing decent space for UMKM angkringan, will be analyzed using Islamic legal philosophy with the Maqāṣid al-Sharī'ah (Objectives of Islamic Law) approach and the Maṣlaḥah (Public Benefit) principle. This research method uses a normative juridical method by examining and evaluating legal norms (Regent's Regulation) using philosophical norms (Islamic Legal Philosophy). The results of the review show that the permit granting policy made by the regent is in line with the objectives of Islamic law in safeguarding property (ḥifẓ al-māl), maintaining order (Maṣlaḥah al-‘Āmmah), and supporting the economic growth of the people, as long as its implementation does not disrupt basic public functions and public order.